Economic Life in Refugee Camps. (July 2017) - Alloush, Mohamad; Taylor, J. Edward; Gupta, Anubhab; Rojas Valdes, Ruben Irvin; Gonzalez-Estrada, Ernesto
Highlights: When people are uprooted from their homelands and resettled into camps, refugee economies arise. Structures of surrounding host economies and human capital shape refugees' economic outcomes. Interactions with the host country economy cause refugees' income and aid to diverge. A shift from in-kind aid to cash increases refugee welfare. Summary: We analyze economic life in three Congolese refugee camps in Rwanda and the interactions between refugees and local host-country economies within a 10-km radius around each camp. Refugees in one of the three camps received food aid in kind, while in the other two camps they were given cash via cell phones provided by the UN World Food Programme. We find that refugee economies arise inside each camp, and the structure of these economies reflects the economic context around the camps. Despite undergoing forced migration and often living in destitute conditions, refugees actively interact with host country economies. Interactions with the host country result in a divergence of refugee households' income from the assistance they receive. A shift from in-kind to cash aid appears to increase refugee welfare while strengthening market linkages between camp and host economies. This finding is potentially important for refugee policies as well as for other types of development assistance, as donors find themselves under pressure to shift from in-kind to cash aid.